Pola Pembinaan Karakter Islami pada Anak Broken Home di Panti Asuhan Aneuk Nanggroe Aceh Besar - Asman, Yunita; Anida, Anida; Muhammad, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Proper education is the right of every child, including children from broken homes. Islamic character building is important for broken home children as an effort to lead to a better life for them. However, this must be conveyed properly so that the teaching of Islamic character can be accepted by broken home children. The purpose of this research is to see the pattern of developing Islamic character in broken home children which is applied at the Aneuk Nanggroe Orphanage. Orphanages This research uses qualitative research with the subject of the Head of the Orphanage and caregivers of children from broken home families in orphanages. Data collection is done through observation, interviews, and documentation. The results showed that the coaching patterns applied by caregivers were: permissive patterns, democratic patterns, by giving advice, using experience patterns, and by applying habits. The obstacles are: a). Internally, namely emotional, lack of motivation, loner, likes to be alone, give up, and cry. b). Externally, namely the lack of parental attention, the lack of female caregivers, the lack of professional caregivers and the lack of training in caring for children to caregivers.